Seismic Amplification by Deep Subsurface and Proposal of a New Proxy - Nagao, T. (Engineering, Technology & Applied Science Research, 2020)
Codes of practice and ground motion prediction equations involve ground structure proxies to account for seismic amplification. Although the ground consists of both shallow and deep subsurface, proxies are mainly related to the shallow subsurface as it is shallow subsurface information that is mostly available. However, as deep subsurface seismic amplification is not negligible, it may not be appropriate to use shallow subsurface proxies. In this study, the relationship between shallow and deep subsurface seismic amplification factors is discussed on the basis of S-wave velocity profile data from Japanese KiK-net strong-motion observation system stations. The correlation between typical proxies such as the average S-wave velocity of the top 30m of the ground surface and the seismic amplification factor was examined. Although there was a negative correlation between the two, the degree of the correlation was weak. A new proxy showing stronger correlations with the seismic amplification factor is proposed and its effectiveness is demonstrated.